People, Justice, and Legitimacy: A Philosophical Review of Sovereignty from the Perspective of John Rawls : Rakyat, Keadilan, dan Legitimasi: Tinjauan Filosofis atas Kedaulatan Perspektif John Rawls - Fajrul Ilmy Darussalam; Andi Batara Indra; Saifur Rahman; Agustan Agustan; Sabaruddin Sabaruddin (Jurnal Pemerintahan dan Politik, 2026)
Objective: To analyze the relevance of John Rawls's social philosophy, specifically justice as fairness and public reason, as a philosophical foundation for the substantive implementation of the concept of popular sovereignty. This study maps the conceptual correspondence between Rawls's two ideas and the four core principles of popular sovereignty, namely the principles of liberty, justice, majority rule, and accountability. Methodology: This study employs library research with a socio-political philosophy approach, encompassing four stages. Findings: Justice as fairness represents the principles of liberty and justice in popular sovereignty through Rawls's two main principles of justice: the guarantee of equal basic liberties for every individual, and the arrangement of social and economic inequalities to the greatest benefit of the least advantaged. Meanwhile, public reason represents the principles of majority rule and accountability by emphasizing that every public decision must be grounded in a collective rationality that embodies the principle of reciprocity and remains accountable to all citizens. Implications: Policy formulation that goes beyond the mere will of the majority by integrating the principle of reciprocity to protect the basic rights of all citizens; furthermore, public reason can serve as a basis for advocacy to ensure that citizen participation is not merely procedural, but also substantive and accountable. Originality: Enriches the understanding of popular sovereignty, shifting it from a mere political procedure into a value system rooted in fundamental liberty and the substantive distribution of justice, while simultaneously providing a critical contribution to the development of deliberative democracy theory.